Community Response to the Health Protocols in Organizing Weddings Ceremony During the Covid-19 Pandemic - Rosyid, Ahmad Zaenur; sholihah, Hidayatus; Cholil, Arief (Universitas Islam Negeri Raden Intan Lampung, 2021)
Government regulations regarding health protocols during the Covid-19 pandemic have resulted in many impacts and dilemmatic atmosphere in almost all community activities relating to the economic, social, political, and religious fields. This effect can be seen clearly in all community activities, including in the implementation of wedding ceremonies and receptions. This study tries to identify the impact of these regulations on wedding traditions in the North Coast region of Java, precisely in Winong and Pucakwangi sub-districts, South Pati. The research focuses on two types of activities, namely the process of wedding ceremony and the wedding reception. This qualitative research uses a socio-normative approach. Data were collected through interviews, observation, and documentation which were then analyzed using qualitative descriptive analysis. Interviews were conducted with some prospective bride and groom couples and marriage registrats in the local area. This study found that citizens, starting from the general public to the social, political, and religious leaders, tend not to care about the provisions on health protocols regulated by the government. This tendency can be seen in the public's response to these provisions at the time of marriage, which can be classified into three types of groups, namely affirmative, conditional-adaptive, and ignorance